PROFESIONALITAS DAN PERSONALITAS GURU KRISTEN: PENGEMBANGAN SUMBER DAYA MANUSIA BERKARAKTER DAN KOMPETEN MENUJU INDONESIA UNGGUL - Napitupulu, Nurasyah Dewi (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2019)
Many studies assume that the professionalism of teachers is influenced by his personality. Personality is a psychological characteristic that contributes to learning outcomes and academic achievement. However, research that proves this assumption is limited in the domain of Christian teachers as part of teachers inIndonesia. This study aims to analyze the correlation between teachers? personality and professionalism obtained through questionnaires and interviews. The analysis was carried out on 16 Christian teachers participated who were attending the Postgraduate Program in "Educational Professional Development" instruction. The results of the correlation test using the SPSS Version 21 program showed that Sig. (2-tailed) = 0.042 <0.05. It concluded that there is a positive correlation between the personality and professionalism of Christian teachers. Qualitative analysis is discovered that the teachers' personality is in the criteria of good and very good, as well as their professionality. The lowest percentage of personality is on the positive self-concept indicator (62.9%) with good criteria, whereas professionality is on the self-confidence indicator (64.5%) with good criteria. The results of interviews as the self-assessment be discovered that Christian teachers with high performance are 18.75%; the adjusted teachers are 43.75%; the teachers hopeless are 43.75%, and not giving answering by 25%. It was concluded that assumptions about teachers? personality and professionalism have a proven correlation for Christian teachers participated. Therefore, to improve professionalism as an Indonesian teachers? competence, it has to develop the personality of Christian teachers sustainable. The personality of the Christian teachers is an entity of Christ's character and professionalism is the existence of ability, attitude, and skills based on common sense. The researcher argues that toward a superior Indonesia is marked by teachers who excel in professionalism and personality.